Effect of cold spells and their modifiers on cardiovascular disease events: Evidence from two prospective studies. (1st September 2016) - Sartini, Claudio; Barry, Sarah J.E.; Wannamethee, S. Goya; Whincup, Peter H.; Lennon, Lucy; Ford, Ian; Morris, Richard W.
Abstract: Objective: To investigate effects of cold weather spells on incidence of cardiovascular disease (CVD), and potential effect modification of socio-demographic, clinical, behavioural and environmental exposures. Methods: Data from two prospective studies were analysed: the British Regional Heart Study (BRHS), a population-based study of British men aged 60–79 years, followed for CVD incidence from 1998–2000 to 2012; and the PROSPER study of men and women aged 70–82 recruited to a trial of pravastatin vs placebo from 1997 to 9 (followed until 2009). Cold spells were defined as at least three consecutive days when daily mean temperature fell below the monthly 10th percentile specific to the closest local weather station. A time-stratified case-crossover approach was used to estimate associations between cold spells and CVD events. Results: 921 of 4252 men from BRHS and 760 of 2519 participants from PROSPER suffered a first CVD event during follow-up. More CVD events were registered in winter in both studies. The risk ratio (RR) associated with cold spells was statistically significant in BRHS (RR = 1.86, 95% CI 1.30–2.65, p < 0.001), and independent of temperature level: results were similar whether events were fatal or non-fatal. Increased risk was particularly marked in BRHS for ever-smokers (RR of 2.44 vs 0.99 for never-smokers), in moderate/heavy drinkers (RR 2.59 vs 1.41), and during winter months (RR 3.28 vs 1.25). No increased risk was found in PROSPER. Conclusions: Although CVD risks were higher in winter in both BRHS and PROSPER prospective studies, cold spells increased risk of CVD events, independently of cold temperature, in the BRHS only. Highlights: CVD risks were higher in winter in both BRHS and PROSPER studies of older adults. In BRHS, we found an added impact of cold spells on CVD, independent of temperature. There was an increased susceptibility to cold spells among smokers and drinkers. Findings support UK guidelines on identification of vulnerable older people.